ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) INFLUENCE ON COMPANY VALUES IN INDONESIA - Madeleine Ruth R Manurung; Riani Rachmawati (Sean Institute, 2023)
The emergence of the Covid-19 pandemic has intensified business competition, resulting in stability and decreased stock exchange trading. Stakeholders become more cautious and selective when making decisions. Therefore, companies must disclose quality financial statements to stakeholders in making accurate decisions. This study aims to re-examine the effect of ESG application on company value in Indonesia empirically. The independent variable in this study is the ESG score, where the value of each component is the result of research conducted by Thomas Reuters. In addition, this study also used a dummy variable, where the reference is an ESG index. The results showed that ESG scores and ESG indicepositively influenceon company value. This is also supported by cross-tabulation, which shows differences in ESG scores against companies that are included and not included in the ESG index. The application of ESG to companies can minimize information asymmetry, as well as potential conflicts with stakeholders. In addition, ESG indices are used to address stakeholder concerns about ESG issues, which can signal that it allows stakeholders to be more accurate in assessing companies based on standards specified in the index.